Life in Lockdown - UNICEF Innocenti Research Centre (United Nations)
COVID-19 lockdowns have significantly disrupted the daily lives of children and adolescents, with increased time at home, online learning and limited physical social interaction. This report seeks to understand the immediate effects on their mental health. Covering more than 130,000 children and adolescents across 22 countries, the evidence shows increased stress, anxiety and depressive symptoms, as well as increased alcohol and substance use, and externalizing behavioural problems. Children and adolescents also reported positive coping strategies, resilience, social connectedness through digital media, more family time, and relief from academic stress. Factors such as demographics, relationships and pre-existing conditions are critical. To ensure children and adolescents are supported, the report recommends building the evidence on the longer-term impact of the pandemic on child and adolescent mental health in low- and middle-income countries, including vulnerable populations.